Research Needs in Canadian Industrial Relations: Emerging from the Solitudes - Thompson, Mark (Relations industrielles / Industrial Relations, 1992)
The distinguishing features of the Canadian industrial relations system for research purposes are its fragmentation, its extensive legal regulation, and its pattern of strikes. Research needs should be based on this description of Canadian industrial relations, including the environment of the system, the major actors within the system, the processes of industrial relations, and the results of negotiation. Specific gaps in industrial relations research occur with regard to: 1. the treatment of regionalism or regional variables, 2. managerial policies and their determinants, 3. the theoretical bases of strikes, including noneconomic variables, interindustry variations, strike length, and mid-contract strikes, and 4. day-to-day relations among employees, management, and the union in the workplace. Greater attention to Canadian issues and closer integration with cognate disciplines will focus research efforts more effectively.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor relations; Research; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes